NOVA OCORRÃŠNCIA DO NEMATÃ“IDE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜©ð˜¢ð˜±ð˜ð˜¢ EM CAFEEIRO - Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
NOVA OCORRÃŠNCIA DO NEMATÃ“IDE ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜©ð˜¢ð˜±ð˜ð˜¢ EM CAFEEIRO